1998
DOI: 10.1097/00000539-199805000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Small-Dose Hyperbaric Versus Plain Bupivacaine During Spinal Anesthesia for Cesarean Section

Abstract: A small dose of hyperbaric bupivacaine 0.5% combined with sufentanil used intrathecally during cesarean section offered a more reliable cephalad spread of the spinal block than the glucose-free combination, which was reflected in a lower incidence of hypotension and nausea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 21 publications
0
46
0
3
Order By: Relevance
“…4,[18][19][20] Vercauteren et al used a combination of sufentanil 3.3 lg with plain or hyperbaric bupivacaine 6.6 mg in 2 mL for spinal anesthesia as part of a combined spinal-epidural procedure in cesarean section. 21 In their study, individual variability was pronounced in the plain group, and significantly more patients in the plain group had blocks that were either too high or too low. Although hypotension was more pronounced in the plain group (21% vs. 6% in the hyperbaric group), their overall incidence was 13%, lower than that of other studies using higher doses, and similar to our PHB group (13.9%).…”
Section: Discussionmentioning
confidence: 90%
“…4,[18][19][20] Vercauteren et al used a combination of sufentanil 3.3 lg with plain or hyperbaric bupivacaine 6.6 mg in 2 mL for spinal anesthesia as part of a combined spinal-epidural procedure in cesarean section. 21 In their study, individual variability was pronounced in the plain group, and significantly more patients in the plain group had blocks that were either too high or too low. Although hypotension was more pronounced in the plain group (21% vs. 6% in the hyperbaric group), their overall incidence was 13%, lower than that of other studies using higher doses, and similar to our PHB group (13.9%).…”
Section: Discussionmentioning
confidence: 90%
“…Several previous studies 2, 16,17 have demonstrated that a low dose of spinal local anaesthetic is associated with a low incidence of hypotension. However, these studies were flawed because of the lack of a control group.…”
Section: Discussionmentioning
confidence: 95%
“…Mit nur 60,8% ist die Rate der Opioidbeimischung in Deutschland verbesserungswürdig. Bezüglich der Barizität des Lokalanästheti-kums gibt es Daten, die eine bessere Zuverlässigkeit und Steuerung der Blockadeausdehnung der hyperbaren Lösung insbesondere im Niedrigdosisbereich bei SC belegen [13,25].…”
Section: Lokalanästhetikaunclassified